Examination techniques in orthopaedics - Harris, Nick, 1965-; Ali, Fazal, 1962- (Cambridge Medicine, 2014)
Comprehensive, easy-to-read guide to clinically examining the musculoskeletal system, helping readers to develop good technique for everyday practice and exams.